Ahıskan, Migration and Education - Hüseyin Hüsnü Bahar; Oğuzhan Yılmaz (Anı Publishing, 2018)
It is a phenomenological study that attempts to determine the educational problems of secondary school students migrating from Ukraine to Erzincan according to their teacher and student opinions. For the study, 10 teachers and 17 students have been consulted in schools where Ahıskan students are educated. The research data gathered with the help of the semi-structured questionnaire was uploaded to the NVivo 11 program and its content analysis was conducted following the descriptive analysis. Encodings made by the researchers during the analysis were categorized by two researchers in cooperation under the headings of program, discipline in school, difference of level- education in the same class, friendship relations, language, family structure and indifference. As a result of the study, Ahiskan Turks migrating from Ukraine to Uzumlu and having been in secondary school have experienced myriad educational problems and many of these problems have been tried to be solved but it was found that they should be more selfless in order to plan the future better and avoid raising lost generations.